2021
DOI: 10.1021/acsami.0c20617
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Fabrication of Hollow Porphyrinic MOF Nanoparticles with Ultrahigh Drug Loading toward Controlled Delivery and Synergistic Cancer Therapy

Abstract: Hollow nanostructures have attracted significant research interest in drug delivery systems due to their high capacities for drug loading and unique physicochemical properties, showing great potential in specific biomedical applications. Herein, hollow porphyrinic metal–organic framework (H-PMOF) nanoparticles with a mesoporous spherical shell have been fabricated via a facile self-sacrificial ZIF-8 nanoparticle template strategy. The H-PMOF nanoplatform not only demonstrates a greatly enhanced photodynamic th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
116
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(117 citation statements)
references
References 51 publications
1
116
0
Order By: Relevance
“…The higher porosity and larger specific surface areas of hollow MOFs than solid counterparts endow the opportunity for the efficient adsorption and storage of drug molecules [66][67][68]. Tian and co-workers constructed a multifunctional platform by using a hollow porphyrinic meal-organic framework (H-PMOF) nanoparticle as the drug carrier [67]. DOX and indocyanine green were loaded with an ultrahigh loading capacity of 635%, higher than that of the nonhollow PMOF.…”
Section: Metal-organic Frameworkmentioning
confidence: 99%
“…The higher porosity and larger specific surface areas of hollow MOFs than solid counterparts endow the opportunity for the efficient adsorption and storage of drug molecules [66][67][68]. Tian and co-workers constructed a multifunctional platform by using a hollow porphyrinic meal-organic framework (H-PMOF) nanoparticle as the drug carrier [67]. DOX and indocyanine green were loaded with an ultrahigh loading capacity of 635%, higher than that of the nonhollow PMOF.…”
Section: Metal-organic Frameworkmentioning
confidence: 99%
“…Hollow gold nanostructures have high photothermal conversion effects and excellent biocompatibility, can adjust the LSPR band in near-infrared (NIR) regions, and are suitable for drug delivery. The irradiation of gold nanoparticles with NIR lasers can accelerate the release of cargo by generated hyperthermia to the target location and ablate the tumor cells with favorable PTT ( Gan et al, 2019 ; Sun et al, 2021 ).…”
Section: Biomedical Applications Of Hollow Gold Nanostructuresmentioning
confidence: 99%
“…24,25 Under laser irradiation, the ICG also produces photodynamic (PDT) effects, therefore PDT and PTT are oen combine used. [26][27][28][29] Nevertheless, researchers were more inclined to study ICG-based PTT since ICG produces stronger photothermal effect. Besides, the poor optical and thermal stability of ICG as PTN limited its further applications.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] Studies have shown that the polymer encapsulated clinical ICG nanoparticles can not only increase the stability of nanoparticles, but also could enhance PDT/PTT effect, meanwhile strengthen biocompatibility of the NPs with negligible toxicity. [27][28][29] Poly(styrene-co-maleic anhydride) (PSMA) is an amphiphilic polymer 40 and oen selected as encapsulation matrix for organic dyes to increase their chemical stability and biocompatibility. [41][42][43][44][45] In addition, PSMA has been used clinically and its covalent binding to proteins has been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation